Modification of the surface chemistry of activated carbon and its influence on methylene blue adsorption - Wibowo, David; Setyadhi, Lanny; Ismadji, Suryadi (Jurnal Teknik Kimia Indonesia, 2006)
The adsorption behavior of activated carbons is determined not only by their porous structures but also by the chemical nature of its surface. The surface chemistry of activated carbons can be selectively modified in order to improve their adsorption capacity. In this study, a NORIT granular activated carbon was treated by oxidant (HNO3) and non-oxidant acid (HCI) at different concentrations and temperatures. The surface chemistries of the materials were characterized by Boehm titration method and by the determination of the point of zero charge (pHPZC).The adsorption properties of the selected samples were studied by adsorption of methylene blue, which is one of the important dyes and found in many textile effluents. In addition, the pore structures of the modified carbons were also studied by argon adsorption at 87.29 K. As results, it was observed that both HN03 and HCI treatments could increase the surface acidity of activated carbons. Activated carbons modified by HCI gave the best performance on the adsorption of methylene blue.Keywords: Activated Carbon, Surface Chemistry, Chemical Treatment, Boehm Titration Method, AdsorptionÂ AbstrakKemampuan adsorpsi karbon akti.ftidak hanya ditentukan oleh struktur pori tetapijuga dipengaruhi oleh sifat kimia dari permukaannya. Sifat kimia permukaan karbon aktif dapat secara selektif dimodifikasi dengan tujuan untuk lebih meningkatkan kapasitas adsorpsinya. Pada penelitian ini, karbon aktif NORIT granular ditreatment dengan menggunakan asam oksidator (HNO) dan non-oksidator (HCI) pada berbagai konsentrasi dan suhu. Sifat kimia permukaan karbon aktif dikarakterisasi dengan menggunakan metode titrasi Boehm serta dengan penentuan point of zero charge (pHPZC). Kemampuan adsorpsinya diuji dengan mengadsorp larutan methylene blue, dimana methylene blue merupakan salah satu komponen dalam limbah tekstil. Sedangkan struktur pori karbon aktif dianalisa dengan adsorpsi Ar pada suhu 87,29 K. Penelitian ini menunjukkan bahwa baik treatment dengan HNO3 maupun HCI dapat mengakibatkan terjadinya peningkatan sifat asam pada permukaan karbon aktif. Karbon aktif yang diberi perlalatan dengan HCI memberikan kemampuan adsorpsi yang paling baik dalam adsorpsi larutan methylen biru.Kata Kunci: Karbon Aktif, Sifat Kimia Permukaan, Perlakuan dengan Larutan Kimia, Metode Titrasi Boehm, Adsorpsi